The Role of French Revolution Fan Discussions on Tumblr in Shaping Contemporary French Political Discourse - Ma Jingyang (SHS Web of Conferences)
History fandom gathers people who discuss and produce narratives of history. Through media participation, history fandom has risen to attract mainstream attention. Meanwhile, political campaigns on media increasingly converge with fandom mobilization, many of which rely on narrating history to convey their ideas. However, whether and how history fandom has influenced the political discourses on media has not been researched. To explore the potential development of these two domains, this article studied the fan discussions of contemporary politics in the French Revolution fan community on Tumblr. With discourse analysis of the language and power background of history fans’ blogs that are relevant to contemporary French politics, this article demonstrated the capability and limitation of fans’ narratives of history in influencing mainstream politics. Shaped by Tumblr’s platform ecosystem, the fandom has collective political values and bases its history narratives on them to resist the ideologies imposed by existing political structures. Nevertheless, to challenge the structure, history fans need to extend their influence beyond the cultural realm. If political forces and fandom can be further connected by the narration of history, the fans’ immaterial labour can be exposed to mainstream media, allowing fans’ self-emancipatory activities to bring social-political changes.